Implementation of Patient Safety Incident Reporting Using Web-Based Quality Management Information System in Hospital X Tangerang - Jeremia, Andrew; Nadjib, Mardiati (UI Scholars Hub, 2025)
Patient safety incident reporting is a critical component of hospital quality systems. This study evaluated the implementation of a Quality Management Information System (QMIS) for incident reporting at Hospital X using the Structure–Process–Outcome (SPO) framework integrated with the HOT-Fit model. A mixed-methods case study was conducted, combining analysis of 774 incident reports submitted between March 2023 and December 2024 with in-depth interviews involving clinical staff, unit heads, and the Quality and Risk (QR) Manager. Findings revealed that while structural elements such as computing infrastructure and leadership support were in place, gaps remained in staff training, procedural awareness, and system usability. QMIS was actively used for reporting, but advanced features like root cause analysis (RCA) and dashboards were underutilized. Reporting performance was moderate, with 62.8% of reports submitted within 24 hours and a reporting rate of 22.03 per 1,000 patient days, below international benchmarks. Although some process improvements were implemented, feedback loops to frontline staff were limited. To enhance system effectiveness, technical improvements are recommended, including interface simplification, mobile access, data validation, and integration with hospital systems. Strengthening local support and fostering a learning-oriented safety culture is also essential to sustain engagement and improve patient safety outcomes.